우리나라 성인의 제한성 및 폐쇄성 폐질환 유병률과 위험요인 : 2019 국민건강영양조사 자료분석 - 이도연(Do-Youn Lee) (한국콘텐츠학회 논문지, 24(2), 2024)
본 연구의 목적은 국내 40세 이상 성인의 폐질환 발생율과 질환의 위험요인을 파악하고, 이에 대한 관리를 통하여 폐질환 발생 예방을 위한 기초자료를 제공하는 것이다. 국민건강영양조사 2019년도 자료를 바탕으로 40세 이상 성인 중 폐기능 검사와 건강설문조사 등에 참여한 3,280명을 대상자로 선정하였다. 복합표본 다중로지스틱 회귀분석을 이용하여 폐질환 발생 위험요인을 분석하였다. 분석결과 본 연구대상자의 제한성 폐질환 발생율은 12.9%로 나타났고, 폐쇄성 폐질환은 10.0%로 나타났다. 제한성 폐질환에서는 남성일수록, 연령대가 높을수록, BMI와 허리둘레를 기준으로 비만인 경우에 발생 위험률이 높게 나타났다. 폐쇄성 폐질환에서는 남성인 경우, 연령대가 높은 경우, 과거흡연 및 현재 흡연자인 경우에 발생 위험률이 높았다. 따라서, 폐질환 발병을 감소시키기 위하여 질환별 위험요인을 가진 대상자를 위한 예방 중재 및 교육이 필요하다. The purpose of this study was to identify the incidence rate and risk factors of pulmonary disease in korean adults. Based on the data from the Korea National Health and Nutrition Survey 2019, 3,280 adults over 40 years of age who participated in lung function tests and health surveys were selected as subjects. Risk factors for lung disease were analyzed using complex sample multiple logistic regression analysis. As a result of the analysis, the incidence of restrictive pulmonary disease of the cases of this study was 12.9%, and obstructive pulmonary disease was 10.0%. The risk of developing restrictive pulmonary disease was high in men, in the high age group, and in the case of obesity based on body mass index and waist circumference. Obstructive pulmonary disease had a high risk of occurrence in men, high age group, past and current smokers. Therefore, in order to reduce the incidence of pulmonary disease, preventive intervention and education are needed for subjects with risk factors for each disease. KCI Citation Count: 0